A double-cylinder model for bond analysis of deformed bars with eccentric concrete confinement. (December 2022) - Yi, Ju; Wang, Lei; Deng, Ming; Tu, Ronghui
Abstract: Bonding between deformed bar and concrete is critical for the load capacity of reinforced concrete structure. In practical engineering, the deformed bar is always eccentrically embedded in a concrete member instead of concentrically installed in it. In this paper, a double-cylinder model, which considers the additional concrete confinement outside the conventional cylinder of concentric embedment case as an extension of cylinder diameter, is first proposed to model overall concrete confinement effect on the deformed bar for the eccentric embedment case. Thereafter, combining the eccentric concrete confinement with other main influencing factors on the bond, such as friction coefficient, rib height and rib spacing, the ultimate bond strength is predicted for the concrete splitting failure mode. By comparing with the prediction bond strengths and experimental results from previous tests, a series of confinement adjustment factors based on the concentric cases are confirmed for various eccentric situations. As a result, a formula of the concrete confinement transition between the eccentric and concentric cases is obtained based on the least square method. Besides, parametric studies are conducted to study the effects of cover thickness, reinforcing bar diameter, concrete tensile strength on the bond strength between deformed bar and concrete.